Estimating ventilation rates of animal houses through CO2 balance - Liu, Zifei; Powers, W.; Harmon, J. D. (My University, 2016)
The CO2 production rates from various animal species were measured as well as the ventilation rates (VR) in environmental rooms at Michigan State University over the course of 15 studies that considered dietary strategies to alter air emissions, including two dairy cow studies, four steer studies, two swine studies, one Turkey study, four laying hen studies, and two broiler chicken studies. The objectives of this article are to summarize the baseline data on CO2 production from various animal species and determine uncertainties of the CO2 balance approach for estimating VR of animal houses by evaluating the model performance in these studies. In the poultry (broiler, laying hen, and Turkey) and dairy studies, the CO2 production rates per heat production of animals or respiratory quotient (RQ) showed a decreasing trend with increasing animal age or days in milk (DIM). Higher variation in CO2 production rates per heat production of animals were observed in young broiler chicken (<3 weeks) and Turkeys (<10 weeks) and in the dairy cow studies. The modeled and measured CO2 production rates were generally comparable with each other for each species, and the standard deviation of model residuals was about 20% to 30% of the average measured CO2 production rate for each species except dairy cows. By only including data in which the differences between exhaust and inlet CO2 concentrations were larger than 50 ppm, the standard deviations of model residuals were less than 32% of the average measured VR in the broiler, laying hen, swine, and steer studies. Based on the results, when using the CO2 balance approach to estimate VR for broiler, laying hen, swine, and steer operations, a minimum of ten replicate measurements is required to achieve a margin of error less than 20% in modeled VR with 95% confidence. © 2016 American Society of Agricultural and Biological Engineers.
Citation: Liu, Z., Powers, W., & Harmon, J. D. (2016). Estimating ventilation rates of animal houses through CO2 balance. Transactions of the Asabe, 59(1), 321-328. doi:10.13031/trans.59.10235
Keywords: Emission; Heat Production; Metabolic Rate; Respiratory Quotient; Ventilation Rate; Animals